Chronic neuropathic pain severity is determined by lesion level in aquaporin 4-antibody-positive myelitis. Issue 2 (24th November 2016) - Tackley, George; Vecchio, Domizia; Hamid, Shahd; Jurynczyk, Maciej; Kong, Yazhuo; Gore, Rosie; Mutch, Kerry; Woodhall, Mark; Waters, Patrick; Vincent, Angela; Leite, Maria Isabel; Tracey, Irene; et al.
Abstract : Importance: Chronic, intractable neuropathic pain is a common and debilitating consequence of neuromyelitis optica spectrum disorder (NMOSD) myelitis, with no satisfactory treatment; few studies have yet to explore its aetiology. Objective: To establish if myelitis-associated chronic pain in NMOSD is related to the craniocaudal location of spinal cord lesions. Method: (1) Retrospective cohort of 76 aquaporin 4-antibody (AQP4-Ab)-positive patients from Oxford and Liverpool's national NMOSD clinics, assessing current pain and craniocaudal location of cord lesion contemporary to pain onset. (2) Focused prospective study of 26 AQP4-Ab-positive Oxford patients, a subset of the retrospective cohort, assessing current craniocaudal lesion location and current pain. Results: Patients with isolated thoracic cord myelitis at the time of pain onset were significantly more disabled and suffered more pain. Cervical and thoracic lesions that persisted from pain onset to 'out of relapse' follow-up (current MRI) had highly significant (p<0.01) opposing effects on pain scores (std. β=−0.46 and 0.48, respectively). Lesion length, total lesion burden and number of transverse myelitis relapses did not correlate with pain. Conclusions: Persistent, caudally located (ie, thoracic) cord lesions in AQP4-Ab-positive patients associate with high postmyelitis chronic pain scores, irrespective of number of myelitis relapses, lesion length and lesion burden. Although disability correlated with pain in isolation, it became an insignificant predictor of pain when analysed alongside craniocaudal location of lesions.